ADP-ribosyltransferases Parp1 and Parp7 safeguard pluripotency of ES cells. Issue 14 (17th July 2014) - Roper, Stephen J.; Chrysanthou, Stephanie; Senner, Claire E.; Sienerth, Arnold; Gnan, Stefano; Murray, Alexander; Masutani, Mitsuko; Latos, Paulina; Hemberger, Myriam
Abstract: Embryonic stem (ES) cells are in a dynamic equilibrium of distinct functional states, characterized by the heterogeneous expression of critical pluripotency factors and regulated by a spectrum of reversible histone modifications. Maintenance of this equilibrium is a hallmark of pluripotency. Here we find that the ADP-ribosyltransferases Parp1 and Parp7 play a critical role in safeguarding this state by occupying key pluripotency genes, notably Nanog, Pou5f1, Sox2, Stella, Tet1 and Zfp42, thereby protecting them from progressive epigenetic repression. In the absence of either Parp1 or Parp7, or upon inhibition of the ADP-ribosylating activity, ES cells exhibit a decrease in ground state pluripotency as they cannot maintain the typical heterogeneity characteristic of the metastable state. As a consequence, they display a higher propensity to differentiate. These findings place Parp1 and Parp7 at the genetic-epigenetic interface of pluripotency networks, fine-tuning the transcriptional heterogeneity and thereby determining the developmental plasticity of ES cells.